Optimalisasi Pengelolaan Anggaran, Hindari Krisis Fiskal - Jaka Sriyana (Unisia, 2001)
For the first of long term development, Indonesia has achieved successfully the high rate of economic growth. It was caused by the government's effective economic policy. In this period the government applied a deficit fiscal, In which total expenditure is over domestic Income. In fact, the value of deficit tends to be higher each year. A high of deficit fiscal was Indicated by strongly increase In both routine expenditure and public Investment. Uncontrolled deficit fiscal policy and Increasing of government expenditure has negative effects, there were a low efficiency of fiscal management, the higher expenditure leaked, the high cost economy and the huge of foreign debt. To overcome these problems the government must create the new sources of revenue and enlarges tax reform.